Investigating the Factors Governing the Informativeness of Stock Prices Using the DEMATEL Approach - Mohammad Hossein Ramazani Zare; Meysam Arabzadeh; Ali Namaki; Mohammad Alipour (تحقیقات مالی)
Objective: Stock price informativeness refers to the extent to which the market price of a share is informative and contains information about the real and underlying economic conditions of that share. It can be one of the most prominent topics in the field of company investment in developed and developing markets. Several factors can affect stock price awareness. Companies proficient in effectively communicating and disseminating information to investors tend to achieve superior performance in the capital market, often resulting in an increase in their stock prices. Stock price informativeness enables companies and industries to be aware of the latest developments and events related to the capital market and thus, to make intelligent investment decisions. Stock price informativeness denotes the degree to which a share's market price conveys valuable information about its true underlying economic conditions. Accordingly, this study endeavors to enhance our understanding of this domain by evaluating the efficacy of factors that influence stock price informativeness. Accordingly, the purpose of this research is to investigate the effectiveness of factors affecting the informativeness of stock price announcements in companies listed on the Tehran Stock Exchange.Methods: This research employs a mixed-methods approach, combining both qualitative and quantitative methods within an inductive-deductive framework. The research participants in the qualitative part were professors and financial managers. According to the purpose of the research, sampling was done in a purposeful way, using the snowball technique, with a number of 17 individuals. The research's statistical population comprised financial managers from companies listed on the stock exchange. Out of this population, 68 managers in this field participated in the study, selected through the stratified probability sampling method.Results: The data obtained from semi-structured interviews led to the extraction of 41 factors influencing stock price informativeness. In this research, the focus has been on factors that impact other variables, along with factors that are influenced by them. Additionally, it has identified factors that permeate and are receptive to permeation. Based on Dematel analysis, management stability factors, management strategies, board experience, and transaction volume are the most important factors that are both penetrable and penetrant. Among the factors examined, state ownership, political conditions, economic factors, and capital market laws exert the most significant influence. Additionally, factors such as managerial stability, strategic company management, the presence of a strategic plan, and growth expectations have been found to have the greatest impact among the other variables.Conclusion: In this research, the factors affecting stock price informativeness have been identified. "Given that the decisions made by managers and investors hinge on their understanding of stock price information, it becomes imperative for researchers and financial industry executives to place significant emphasis on cultivating this awareness and comprehending the factors that influence it". "Therefore, the researchers of the present study suggest that diversifying ownership, delivering timely and precise financial information to investors, and fostering interaction with shareholders can be instrumental in bolstering investors' trust in the company's management and decision-making".